(untitled) (Jurnal Pelita Pendidikan, 2016)
This study aimed to compare the learning outcomes of students who were taught using STAD model of TPS with the subject matter Coordination System In Humans in Class XI IPA at SMAN 15 Medan. This study comprise the experimental study where the population is all students of Class XI IPA at SMAN 15 Medan, which consists of six classes with the number of 240 people. Random sampling (random sampling) and obtained two classes as a sample of Class XI IPA-5 and Class XI-6 totaling 79 people. Class XI IPA-5 are taught with the model and grade XI TPS-6 is taught with STAD model. The instrument used in this study in the form of multiple choice questions which amount to 25 pieces are used as a matter of pretest and posttest. The average results obtained for classroom learning TPS amounted to 80.51 higher than the class of STAD which amounted to 76.5 so that there is a difference in value by 4.01%. Tests were performed by t test produces t_hitung = 2.409 and T_ (table) = 1,665 with df = 77 and a significance level of 0.05. Based on the criteria H_o acceptable if - t_1 -½ Î± <t <t_1 - ½ Î±, then this study reject and accept. It can be concluded that there are differences in learning outcomes of students who are taught by TPS cooperative model with STAD on the subject matter Coordination System In Humans in Class XI IPA at SMAN 15 Medan and TPS are better than STAD on subject matter Coordination System In Human. Key Word : conventional method, computer-based media, learning outcome.